Comparison of IPAS Learning Media Features In Popular Online Learning Applications - Dika Arief Sugiyatna; Casmat, Memet; Suryo Prabowo (LPPM Universitas Terbuka, 2025)
This study aims to compare the features of IPAS (Natural and Social Sciences) learning media on several popular online learning applications used in Indonesia. The methods used were literature studies and content analysis of three applications, namely Ruangguru, Rumah Pendidikan and Kipin School. Data was collected through direct observation of the display, media type, interactivity, and IPAS materials available on each platform. The results of the analysis show that each application has its own advantages, such as the animated video feature in Ruangguru, free access and national curriculum materials at the Education House, as well as offline formats and interactive quizzes at Kipin School. The conclusion of the study is that no one app is superior, however users can choose according to their needs and technical conditions. The purpose of this research is to provide a reference for teachers, students, and application developers in selecting or developing effective IPAS learning media